IMPACT OF POLYPHARMACY ON THE HEALTH OF THE ELDERLY PERSON: NURSING STRATEGIES - Mascarenhas, Beatriz Ornelas; Honorato, Isadora Souza; Fonseca, Millena Gomes; Ramos, Daniele Pereira; Silva Neto, Luiz Sinésio; Silva, Kaiê Wolney Santana; dos Santos, Vanessa Gomes Matos; Souza, Genilcilene Brito da Conceição (Seven Editora, 2026)
Objective: To analyze the impacts of polypharmacy on the health of elderly people and the nursing strategies for the prevention of adverse events. Methodology: This is an integrative literature review, conducted in the Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed), SciELO, and Google Scholar databases, considering publications from 2020 to 2025. Controlled descriptors from DeCS were used, combined by Boolean operators: Elderly (Aged) AND Polypharmacy (Polypharmacy) AND Nursing Care (Nursing Care). Results: A total of 225 studies were identified in the databases. After applying the inclusion and exclusion criteria and reading titles and abstracts, 33 articles remained. After removing duplicates, 27 studies were selected for full-text reading, resulting in a final sample of 12 articles that met the research objective. Conclusion: Polypharmacy constitutes an important challenge for the health of the elderly population, being a multifactorial phenomenon associated with the presence of chronic diseases, physiological aging, and vulnerabilities in healthcare. The fundamental role of nursing in preventing adverse events is highlighted, through strategies such as nursing consultations based on the Nursing Process, health education, and the Systematization of Nursing Care, contributing to safer care and the improvement of the elderly person’s quality of life.